2011
DOI: 10.2169/internalmedicine.50.4424
|View full text |Cite
|
Sign up to set email alerts
|

Study of Folate Status Among Egyptian Asthmatics

Abstract: Objective To compare serum folate levels between atopic asthmatics, non-atopic asthmatics, and healthy controls. Methods This case-control study included 60 asthmatics with at least one positive skin prick test (SPT) reaction (atopic asthma group), 60 asthmatics with negative SPT reactions (non-atopic asthma group), and 60 healthy controls with no history of asthma or other allergic diseases, and with negative SPT reactions. Serum folate and total IgE levels were measured in all subjects. In addition, lung fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 28 publications
1
24
1
Order By: Relevance
“…Seven cross-sectional studies have yielded conflicting findings for folate and asthma or atopy (15,16,(21)(22)(23)(24) (Table 1).…”
Section: Epidemiologic Studies Of Folate Status and Asthma Or Atopymentioning
confidence: 99%
See 1 more Smart Citation
“…Seven cross-sectional studies have yielded conflicting findings for folate and asthma or atopy (15,16,(21)(22)(23)(24) (Table 1).…”
Section: Epidemiologic Studies Of Folate Status and Asthma Or Atopymentioning
confidence: 99%
“…Although three case-control studies with small sample size (including preschool children [24], adolescents [16], and adults [22]) found no significant association between dietary intake (16) or serum level of folate (22,24) and asthma (16,22) or atopic dermatitis (24), a larger case-control study of 1,030 British adults found a significant inverse association between dietary folate intake and physician-diagnosed asthma (adjusted [a] odds ratio [OR] for each quintile increase in intake ¼ 0.89, 95% confidence interval [CI] ¼ 0.81-0.98) (25). In contrast to findings from case-control studies, a cross-sectional study of 1,601 Australian adults showed that dietary intake of folate was positively associated with having ever had physician-diagnosed asthma (OR for each mg ¼ 2.2, 95% CI ¼ 1.2-3.9) but not with current asthma, airway responsiveness, or atopy (23).…”
Section: Epidemiologic Studies Of Folate Status and Asthma Or Atopymentioning
confidence: 99%
“…Recent studies suggest that folate may influence the risk of developing atopy and lower respiratory tract disease in children 1 and adults, 24 but there have been no studies, to our knowledge, that examine the relationship between folate status and allergic inflammation and asthma control among individuals with established disease. Because population-based data have shown an inverse association between serum folate levels and atopy, 2 wheeze, 2,3 and asthma, 3 it is plausible that serum folate levels may also be inversely associated with these outcomes among individuals with established asthma.…”
Section: To the Editormentioning
confidence: 99%
“…Similarly, serum folate was inversely associated with total IgE in a study of 120 adults with asthma (10). In contrast to findings from those cross-sectional studies (9, 10), a multivariate analysis of data from a 1-year prospective study of 144 children with persistent asthma (aged 5-17 yr) showed that serum folate was not significantly associated with symptoms or acute visits for asthma, lung function, fractional exhaled nitric oxide, number of positive skin tests to allergens, or asthmarelated hospitalizations; although folate level was significantly but nonlinearly associated with total IgE, such finding is of unclear relevance, given all other negative results.…”
Section: Original Researchmentioning
confidence: 97%
“…This question is relevant, given results of a recent metaanalysis of 11 observational studies, which showed that high dietary intake of vegetables (a source of folate) is associated with 11% reduced risk of wheeze in children and adults (8). Moreover, folate deficiency or a low folate level has been associated with increased risks of wheeze, atopy, or an elevated total IgE in cross-sectional studies of children and adults (9,10).…”
mentioning
confidence: 99%